Hursery care in breast's cancer and sentinel lymph node: a qualitative approach to health's team - Elaine Cristina Carvalho Moura; Gerdane Celene Nunes de Carvalho; Grazielle Roberta Freitas da Silva (Universidad de Alicante, 2012)
The present study aims analyzes the nursery care on health's team and the perspectives in the treatment of breast's Cancer by detection of the sentinel node. Treated of a descriptive qualitative research with data picked up through route semi structured applied to seven doctors and three nurses, chosen according to the professional experience in the thematic in focus, and discussed by the analyzes of content technique. The results point that this technology is constituted by stages and process that need the intervention of a health's team specifically demanded a nursing planning, updating and nursery care individual. Concluded that the sentinel node develops as qualitative change in the rehabilitation and women's recovery, deserving prominence the engagement of the health's team through which Knowledge are articulate in new Knowledge, resulting in benefits for the woman's health and, above all, opening a new area of actuation to Nurse "the nuclear nursing".